anonymous
  • anonymous
Can someone explain the substitution method for literal equations?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
amistre64
  • amistre64
do you have n example we can work thru?
anonymous
  • anonymous
Hold on
anonymous
  • anonymous
x - y = 4 4y - x = 14

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

amistre64
  • amistre64
to substitute means to replace with an equal value right?
amistre64
  • amistre64
x-y = 4 ; lets solve for x by +y to each side x-y+y = 4+y x+0 = 4+y x = 4+y ; this is an equal value for x; we use it in the other equation now
anonymous
  • anonymous
The 3 rules I have are 1. Solve one of the equations for x or y 2. Substitute this expression into the other equation and solve for one unknown. 3. Place this value back into one of the equations and determine the other unknown.
amistre64
  • amistre64
4y - x = 14 4y -(4+y) = 14 ; distribute the - thru the (...) 4y -4 -y = 14 ; +4 to each side 4y -4+4 -y = 14+4 4y -y = 18 ; add your y's together 3y = 18 ; solve for y by /3 to each side y = 6
amistre64
  • amistre64
since y = 6 is a solid value; we can use it in our equation to find x recall that: x = 4+y ; and we now know that y = 6 x = 4+6 = 10
amistre64
  • amistre64
you can put it back into another equation if you want, but why bother with that since you already found an equation for x :)
anonymous
  • anonymous
Thanks again!
amistre64
  • amistre64
youre welcome...again :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.